1995
DOI: 10.2118/25271-pa
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Wettability on Waterflooding: Pore-Scale Simulation

Abstract: Summary This paper describes the development and implementation of a pore-scale simulator into which pore-wettability effects have been incorporated. Relative permeability and capillary pressure curves from this steady-state model have been analyzed to allow better interpretation of experimental observations from a microscopic stand-point. The simulated capillary pressure data demonstrate that some standard wettability tests (such as Amott-Harvey and free imbibition) may give misleading resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(40 citation statements)
references
References 15 publications
4
36
0
Order By: Relevance
“…Insight into displacement mechanisms is provided by increasingly versatile deterministic network models (84)(85)(86)(87)(88). There is growing interest in the development of rules for pore level displacement that apply to multiphase flow.…”
Section: Discussionmentioning
confidence: 99%
“…Insight into displacement mechanisms is provided by increasingly versatile deterministic network models (84)(85)(86)(87)(88). There is growing interest in the development of rules for pore level displacement that apply to multiphase flow.…”
Section: Discussionmentioning
confidence: 99%
“…Pore-network modeling has advanced to a veritable theoretical compliment to special core analysis and has proved to be an efficient tool to study the effect of wettability at the macroscopic scale, especially on oil recovery (McDougall and Sorbie, 1995;Blunt, 1998;DiCarlo et al, 2000;Zhao et al, 2010;Ryazanov et al, 2014). It is being used in the industry to assign multiphase flow properties in reservoir models and to predict how these properties vary with rock type and wettability.…”
Section: Pore Network Modelsmentioning
confidence: 99%
“…It has been shown that temperature and oil viscosity also affect the distribution of fluids in the pore spaces, and hence wettability distribution (Alhammadi et al, 2017). McDougall and Sorbie (1995) investigated trends in relative permeability and oil recovery efficiency as functions of wettability with a regular cubic network. Recovery was shown to be maximum in a network where half the pore space was oil-wet.…”
Section: Applications Of Pore-network Modelingmentioning
confidence: 99%
“…Another approach is to ignore the detailed structure of the porous medium and simply to represent the microstructure by an interconnected network based on the assumption that larger pores (pore bodies) are connected by smaller pores (throats) (Fatt, 1956;Kantzas et al, 1988;Øren and Pinczewski, 1992;McDougall and Sorbie, 1995;Blunt et al, 1995;Keller et al, 1997;Øren et al, 1994;Pereira et al, 1996;Mani and Mohanty, 1998;van Dijke and Sorbie 2002). Within such network models, it is possible to define a distribution of pores and throats so that the model reproduces various aspects of two-and three-phase flow behaviour.…”
Section: Introductionmentioning
confidence: 99%